(Acetato-kappa O)(2,5,5,7,9,12,12,14-octamethyl-1,4,8,11-tetraazacyclotetradecane-kappa N-4,N `,N `',N `'')zinc perchlorate - Roy, T.G.; Hazari, S.K.S.; Barua, K.K.; Tiekink, E.R.T. (International Union of Crystallography, 2011)
The Zn-II atom in the cation of the title salt, [Zn(C2H3O2)(C18H40N4)]ClO4, is five-coordinated by the four N atoms of the macrocycle and the O atom of the monodentate acetate ligand. The N4O donor set is based on a trigonal bipyramid with two N atoms occupying axial positions [N-Zn-N = 170.89 (16)degrees]. The perchlorate anions are associated with the cations via N-H center dot center dot center dot O hydrogen bonds; intramolecular N-H center dot center dot center dot O(acetate) interactions are also observed. The neutral aggregates are connected into an helical chain along the b axis via N-H center dot center dot center dot O(acetate) hydrogen bonds. The perchlorate anion was found to be disordered about a pseudo-threefold axis: the major component of the disorder had a site occupancy factor of 0.692 (11).